How do you simplify the expression cost/(1+sint)+cost/(1-sint)?
1 Answer
Aug 27, 2016
Explanation:
Begin by expressing the sum of the 2 fractions as a single fraction. This requires having a common denominator.
rArr(cost)/(1+sint)xx(1-sint)/(1-sint)+(cost)/(1-sint)xx(1+sint)/(1+sint)
=(cost(1-sint)+cost(1+sint))/((1+sint)(1-sint)) distributing the brackets on numerator and denominator
=(cost-costsint+cost+costsint)/(1-sin^2t)
color(orange)"Reminder " color(red)(|bar(ul(color(white)(a/a)color(black)(sin^2t+cos^2t=1rArr1-sin^2t=cos^2t)color(white)(a/a)|))) simplifying numerator/denominator gives.
(2cost)/(cos^2t)=(2cancel(cost)^1)/(cancel(cost)^1cost)=2/cost=2sect
color(orange)"Reminder " color(red)(|bar(ul(color(white)(a/a)color(black)(sect=1/cost)color(white)(a/a)|)))
rArr(cost)/(1+sint)+(cost)/(1-sint)=2sect